If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1y = (x) 7x + -1y = x Solving 7x + -1y = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 7x + -1x + -1y = x + -1x Combine like terms: 7x + -1x = 6x 6x + -1y = x + -1x Combine like terms: x + -1x = 0 6x + -1y = 0 Add 'y' to each side of the equation. 6x + -1y + y = 0 + y Combine like terms: -1y + y = 0 6x + 0 = 0 + y 6x = 0 + y Remove the zero: 6x = y Divide each side by '6'. x = 0.1666666667y Simplifying x = 0.1666666667y
| 0.5(x+2)-(3x+8)=1.6(x-2)+9 | | 3(7x+20Y)+7(-3x+6y)= | | y-37=-67 | | -21=n-10 | | 2(2x+5)=40 | | 3(x-5)=2(x+1)+x | | 5+9x=-13 | | -5.7-44.2=-8.3v | | -7y+3=8y+1 | | 3(7x+20Y)7(-3x+6y)= | | 4x+8-3x-10=-33 | | -6-2x-1=4x+8-6x-3 | | 2(n+5)=11 | | 7=-11+3(6+5) | | 2(n+5)=111 | | -5r-r=5r-8 | | 3x+5x+4x-2=10 | | -10x+8-6x=-2-17x+9 | | 5.4x+8.6=3.4x-16 | | (10+2x)(20+2x)=336 | | 7x+6=3x+2 | | 2x-16y=7 | | 6(6g-2)+8(1+5g)=2g | | 6n-32=3n+7 | | 2x^2-4x=1.33333 | | 7t-6=330 | | (7+u)(5u-6)=0 | | 7x+8x+2x=12 | | -69=6(-3n-2)-(-5n-8) | | 19=x-32 | | A(-8)= | | 2y=x+13 |